Perinatal Arterial Stroke Treated With Stromal Cells Intranasally: 2-Year Safety and Neurodevelopment - Wagenaar, Nienke; Baak, Lisanne M.; van der Aa, Niek E.; Groenendaal, Floris; Dudink, Jeroen; Tataranno, Maria Luisa; Koopman, Corine; Verhage, Cornelia H.; Eijsermans, Rian M.J.C.; van Teeseling, Heleen C.; Smit, Liesbeth S.; Jellema, Reint K.; et al. (Stroke (1970), 2025)
BACKGROUND: The PASSIoN study (Perinatal Arterial Stroke Treated With Stromal Cells Intranasally) demonstrated the feasibility and short-term safety of single-dose allogeneic mesenchymal stromal cells (MSCs) administered intranasally to neonates with perinatal arterial ischemic stroke between February 2020 and April 2021. In this study, we assessed long-term safety and neurodevelopmental outcomes and explored outcome differences with a non-MSC-treated cohort. METHODS: In this post hoc analysis, we evaluated the safety of MSC administration by assessing brain tissue loss, adverse events, and neurodevelopmental outcomes of PASSIoN participants (N=10). The tissue loss ratio was calculated using semi-automatic segmentation based on neonatal and 3-month magnetic resonance imaging. At the age of 2 years, we assessed the occurrence of cerebral palsy, motor and cognitive delays (Z score <−1 SD), behavioral and language problems, visual field defects, and epilepsy. We selected a non-MSC-treated registry cohort (N=39) born between 1994 and 2022, who would have met PASSIoN trial inclusion criteria to compare magnetic resonance imaging and outcome characteristics. RESULTS: At 3 months, the mean±SD tissue loss ratio of PASSIoN participants was 89±21%, indicating more preserved tissue than expected based on initial stroke volume. By the age of 2 years, no related adverse events were reported. Two children (20%) developed cerebral palsy (Gross Motor Function Classification System I) without motor developmental delays. Cognitive, behavioral, and language problems affected 10% to 20%, and none had developed epilepsy. Compared with the registry cohort, and PASSIoN participants showed less often asymmetry of the posterior limb of the internal capsule (40% versus 81%; P=0.02) and the cerebral peduncle (10% versus 61%; P=0.01) on 3-month magnetic resonance imaging and had a better motor performance at the age of 2 years (median [interquartile range] Z score, 0.3 [0.8] versus −0.4 [1.5]; P=0.003). CONCLUSIONS: This study demonstrates the long-term safety of intranasal MSC therapy in 10 infants with perinatal arterial ischemic stroke and may suggest better motor outcomes compared with the literature and a non-MSC-treated cohort. Randomized controlled trials are required to confirm MSC efficacy for children with perinatal arterial ischemic stroke. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT03356821.